Time varying CAPM betas and banking sector risk - Caporale, Tony (Economics letters, 2012)
This paper employs the Bai and Perron (1998, 2003) structural break methodology to investigate whether the CAPM betas for banking sector stocks are time invariant. I find evidence for three large structural shifts in my monthly (1941.02–2008.01) sample. The third break corresponds with a decline in the perceived riskiness of banking stocks in the period starting in 2000.04. The banking sector was thus priced to be less risky during the period associated with rising leverage and financial sector risk. ► CAPM Betas for the S&P Banking Stock Index vary significantly over time. ► A low beta regime begins in 2000.5. ► Banking stocks were priced as low risk investments during the period associated with increased risk taking and leverage.